2008
DOI: 10.1021/ja8040493
|View full text |Cite
|
Sign up to set email alerts
|

How the π Conjugation Length Affects the Fluorescence Emission Efficiency

Abstract: How the pi conjugation length affects the fluorescence emission efficiency is elucidated by examination of the theoretical and experimental relationship between absolute quantum yield (Phi(f)) and magnitude (Api) of the pi conjugation length in the excited singlet state, which provides a novel concept for molecular design for highly fluorescent organic compounds. As a tool to predict Phi(f) from a structural model, (nu(a) - nu(f))1/2 x a3/2 (nu(a): wavenumber of absorption maximum, nu(f): wavenumber of emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
194
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 19 publications
8
194
0
2
Order By: Relevance
“…[30] Recently, a rudimentary definition of the effective conjugation length (A p ) made use of Equation (1), in which b is an unspecified constant taken to equal unity. [31] Although there is a smooth evolution of F F with the A p value computed from Equation (1), this is not a useful definition of the effective conjugation length for molecular systems. Indeed, there is no global correlation between A p and, for example, the emission maximum, although the data derived for the B series do show a smooth evolution.…”
Section: Resultsmentioning
confidence: 99%
“…[30] Recently, a rudimentary definition of the effective conjugation length (A p ) made use of Equation (1), in which b is an unspecified constant taken to equal unity. [31] Although there is a smooth evolution of F F with the A p value computed from Equation (1), this is not a useful definition of the effective conjugation length for molecular systems. Indeed, there is no global correlation between A p and, for example, the emission maximum, although the data derived for the B series do show a smooth evolution.…”
Section: Resultsmentioning
confidence: 99%
“…We have also used extended conjugated active methylene but we got the rearranged product. All the final products were carefully purified and fully characterized by 1 H NMR, 13 C NMR and HRMS, which confirmed the expected molecular structures. The 1 H NMR spectra of the dye COS4 showed doublet peaks at 7.90 ppm and at 6.91 ppm having trans vicinal coupling constant (J = 15.5 Hz) which indicates that the olifinic protons at π-bridge are in trans form.…”
Section: Chemistrymentioning
confidence: 62%
“…Due to this limitation there is need to develop luminescent molecules with strong solid state and aggregate state emission properties. In the last decades, AIE molecules involving intramolecular restriction [11,12], planarity and rotation ability [13], twisted intramolecular charge transfer (TICT) [14][15][16] have been reported, since the first report of AIE material by Tang and co-workers in 2001 [17]. In recent years, variety of fluorophores have been designed and synthesized with conjugated [18] and twisted skeleton to exhibit AIE [12,19].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] It has been reported that the uores-cence emission efficiency is affected by the p-conjugation length of compounds. 28 In the cases of TPE derivatives, the introduction of PAHs can extend the p-conjugation of compounds and their good performance in emission suggests that enlarging the pconjugation degree of AIE compounds is an effective strategy to obtain solid-state dyes. Based on this fact, we speculate that in solid state, intramolecular rotation of AIE compounds can be effectively restricted and p-p interactions are completely absent, whether the emission efficiency would increase with the increasing p-conjugation?…”
mentioning
confidence: 99%